2017
DOI: 10.3171/2016.7.jns16232
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive resection at the infiltrative margins of glioblastoma facilitated by intraoperative fluorescein guidance

Abstract: ABBREVIATIONS 5-ALA = 5-aminolevulinic acid; BBB = blood-brain barrier; CE = contrast enhancing; CUMC = Columbia University Medical Center; EOR = extent of resection; GBM = glioblastoma; GTR = gross-total resection; HGG = high-grade glioma; n-ANOVA = multiway ANOVA; NCE = non-contrast enhancing; OS = overall survival; PFS = progression-free survival; PPV = positive predictive value; ROI = region of interest; STR = subtotal resection; UD = undetermined; WHO = World Health Organization; Y560 = YELLOW 560. OBJECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 36 publications
(39 reference statements)
3
77
2
1
Order By: Relevance
“…These data are similar to that obtained by Murray and colleagues, who systematically studied SF accuracy in tumor identification, performing 186 biopsies in 23 patients with brain malignancies, and obtaining a sensitivity of 96% and a specificity of 81% (48). Furthermore, it has been recently demonstrated that intraoperative fluorescein staining correlated with histologic alteration both in contrast enhanced and in noncontrast enhanced regions, with a sensitivity of 75.6% and a specificity of 75% (41). We are aware that sensitivity, specificity, PPV, and NPV measured in our samples, and in other similar studies, are biased by the conditionality of surgical samples, especially in the peritumoral "healthy" tissue.…”
Section: Discussionsupporting
confidence: 72%
“…These data are similar to that obtained by Murray and colleagues, who systematically studied SF accuracy in tumor identification, performing 186 biopsies in 23 patients with brain malignancies, and obtaining a sensitivity of 96% and a specificity of 81% (48). Furthermore, it has been recently demonstrated that intraoperative fluorescein staining correlated with histologic alteration both in contrast enhanced and in noncontrast enhanced regions, with a sensitivity of 75.6% and a specificity of 75% (41). We are aware that sensitivity, specificity, PPV, and NPV measured in our samples, and in other similar studies, are biased by the conditionality of surgical samples, especially in the peritumoral "healthy" tissue.…”
Section: Discussionsupporting
confidence: 72%
“…Since its introduction, fluorescence-guided tumor resection has been the subject of considerable scrutiny and investigation 510. Intravenously injected FNa accumulates in regions with a disrupted blood–brain barrier secondary to various causes, including the presence of tumor or intraoperative iatrogenic injury.…”
Section: Introductionmentioning
confidence: 99%
“…17 Most studies have demonstrated that the enhancement pattern of fluorescein was similar to the contrast enhancement on MRI. [18][19][20] The typical appearance of fluorescein is to turn the tumor yellowish-green, while the peripheral brain tissue remains in its natural color.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that the enhancing pattern of fluorescein is similar to contrast enhancement due to the mechanism of penetrating the disrupted blood-brain barrier. 19,20 According to our inclusion criteria, every tumor was enhanced on pre-operative MRI. Thus, it is certain that all tumors were stained and illuminated under the microscope.…”
Section: Discussionmentioning
confidence: 99%